Acitretin induced lung injury by differentiation syndrome. (2020) - Khan, Sarah; Guddati, Achuta Kumar; Marak, Creticus
Abstract: Differentiation syndrome is a life-threatening complication observed when retinoic acid is given to patients with acute promyelocytic leukemia. Retinoid compounds are also used in non-malignant conditions like psoriasis and it is rare to see differentiation syndrome in such settings. This reports details the clinical presentation and successful management of a patient with psoriasis who developed differentiation syndrome while on treatment with acitretin. The patient was managed with steroids and the differentiation syndrome abated with eventual complete resolution. This report exemplifies the need to consider differentiation syndrome in patients who have non-malignant conditions and are being managed with retoinds.